The Influence of Digital Marketing and E-WOM on Patient Visit Intention with Brand Awareness as an Intervening - Vicky Vicky; Erry Yudha; Wahyuni Dian Purwati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The development of Digital Marketing and Electronic Word of Mouth (eWOM) has encouraged hospitals to adopt digital communication strategies to attract patients’ visit intentions. However, in public hospitals, the effectiveness of these strategies in influencing patient behavior still requires empirical validation. This study aims to analyze the influence of Digital Marketing and eWOM on patient visit intention, with Brand Awareness as an intervening variable at RSUD Cengkareng.This research employed a quantitative approach with an explanatory design. Data were collected from November to December 2025 from 100 general outpatient respondents selected using the Slovin formula and a simple random sampling technique. The data were gathered through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS software.The results show that Digital Marketing and eWOM have a positive and significant effect on Brand Awareness. Both variables also significantly influence patient visit intention, with eWOM demonstrating the strongest effect. These findings indicate that information shared through digital platforms and patient recommendations plays an important role in shaping potential patients’ decisions to visit the hospital. However, Brand Awareness does not have a significant effect on patient visit intention and does not mediate the relationship between Digital Marketing, eWOM, and visit intention. This suggests that, in the context of RSUD Cengkareng as a public hospital, patients’ visit decisions are more directly influenced by digital information exposure and the credibility of online recommendations rather than by brand recognition alone.